Filtration cases of Ugra soldiers participating in the World War II as historical source - E. V. Leshukova (Омский научный вестник: Серия "Общество. История. Современность")
During the 75 years that separate us from the Victory Day on May 9, 1945, a huge array of documentary evidence of the Great Patriotic War is put into scientific circulation. Nevertheless, one of the little-studied sources remains the filtering files of repatriated citizens. The article discusses the circumstances of the appearance and storage of this type of source. Based on a selective comparative analysis there are discovered some details of the content of the filtration cases of military personnel, who went to the front from the territory of the Khanty-Mansiysk Autonomous District of the modern Tyumen Region, informational possibilities of using filtration files for scientific purposes